Pelaksanaan Kursus Biola Di Yamaha Music School Padang - Tri Utari; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2021)
This study aims to determine the implementation of violin courses at Yamaha Music School Padang. The data were obtained during the learning process. Interviews were conducted to violin instructors at Yamaha Music School Padang. In addition, photos during the violin learning process at Yamaha Music School Padang were documented. Based on the research results, the implementation of music courses at Yamaha Music School Padang, especially the violin course,